The Analysis of the Development of Islamic Economic System in Europe with the Increasing Capacity of Muslims as a Minority - Ghozali, Mohammad; Sahid, Mualimin Mochammad; Rohman, Muchamad Zainur (AL- IKTISAB Journal of Islamic Economic Law, 2023)
••• English ••• Islam entered Europe for the first time in 711 M, brought by Tariq bin Ziyad via Spain. In Europe Muslims are still classified as a minority because the largest religion in Europe is Christianity. Able to overcome various existing economic problems, especially the problem of the economic crisis, Islamic economics is present as an alternative to a capitalist economy and socialism. Islam comes with comprehensive and universal teachings. This research aims to discuss in depth the development of the Islamic economic system in Europe, using historical approaches and documentary methods in data collection techniques, namely by analyzing articles that have relevance to the topic being discussed. The conclusion of this research is that in the European continent itself, the development of an economy based on sharia, one of which is a factor in the increasing Muslim population in Europe. The growth and development of the Islamic economy in Europe can also be seen by the birth of Islamic banking, namely 22 banks that have been operating and 6 of them are certified full sharia. Sukuk are also getting more interest and ordering from the public, implants in Europe are listed on the Luxembourg Stock Exchange. The development of Islamic insurance is also relatively fast because it has received a good response from the community. Other progress can be seen from the many scientific studies that discuss the Islamic economic system in several universities, such as at Harvard University. ••• Indonesian ••• Islam masuk ke Eropa pertama kali pada tahun 711 M, dibawa oleh Tariq bin Ziyad melalui Spanyol. Di Eropa umat Islam masih tergolong minoritas karena agama terbesar di Eropa adalah Kristen. Mampu mengatasi berbagai permasalahan ekonomi yang ada, terutama masalah krisis ekonomi, ekonomi Islam hadir sebagai alternatif dari ekonomi kapitalis dan sosialisme. Islam hadir dengan ajaran yang komprehensif dan universal. Penelitian ini bertujuan untuk membahas secara mendalam perkembangan sistem ekonomi Islam di Eropa, dengan menggunakan pendekatan sejarah dan metode dokumenter dalam teknik pengumpulan data, yaitu dengan menganalisis artikel yang memiliki relevansi dengan topik yang sedang dibahas. Kesimpulan dari penelitian ini adalah di benua Eropa sendiri, perkembangan ekonomi yang berbasis syariah salah satunya menjadi faktor meningkatnya populasi Muslim di Eropa. Pertumbuhan dan perkembangan ekonomi Islam di Eropa juga dapat dilihat dengan lahirnya perbankan syariah, yaitu 22 bank yang telah beroperasi dan 6 diantaranya bersertifikat full syariah. Sukuk juga semakin diminati dan diminati masyarakat, implan di Eropa tercatat di Luxembourg Stock Exchange. Berkembangnya asuransi syariah juga tergolong cepat karena telah mendapat respon yang baik dari masyarakat. Kemajuan lain terlihat dari banyaknya kajian ilmiah yang membahas sistem ekonomi Islam di beberapa universitas, seperti di Universitas Harvard.